2012
DOI: 10.1016/j.resuscitation.2011.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside enhanced cardiopulmonary resuscitation (SNPeCPR) improves vital organ perfusion pressures and carotid blood flow in a porcine model of cardiac arrest

Abstract: Purpose of the study To describe a new method of CPR that optimizes vital organ perfusion pressures and carotid blood flow. We tested the hypothesis that a combination of high dose sodium nitroprusside (SNP) as well as non-invasive devices and techniques known independently to enhance circulation would significantly improve carotid blood flow (CBF) and return of spontaneous circulation (ROSC) rates in a porcine model of cardiac arrest. Methods 15 Isofluorane anesthetized pigs (30±1Kg), after 6 minutes of unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…However, another study performed by our group demonstrated incremental benefit to each mechanical component of SNPeCPR by examining them independently. 36 The role of SNP in addition to the mechanical CPR platform of SNPeCPR, has also been established and has been shown to improve neurological intact survival. 10 Finally, in this model the coronary arterial bed was patent, and we are not able to extrapolate these results to an ischemic model of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study performed by our group demonstrated incremental benefit to each mechanical component of SNPeCPR by examining them independently. 36 The role of SNP in addition to the mechanical CPR platform of SNPeCPR, has also been established and has been shown to improve neurological intact survival. 10 Finally, in this model the coronary arterial bed was patent, and we are not able to extrapolate these results to an ischemic model of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…SNPeCPR improved vital organ perfusion pressure, carotid blood flow, and 24h survival with good neurologic outcome in similar studies (10-12, 23). The increase of cerebral blood flow provided by SNPeCPR in combination with improved heat exchange due to the peripheral vasodilation explains the faster cooling rate observed.…”
Section: Discussionmentioning
confidence: 52%
“…The combination of SNP with a mechanical CPR platform [active compression-decompression (ACD) CPR combined with an inspiratory impedance threshold device (ITD) plus abdominal binding] is referred to as SNPeCPR. SNPeCPR has been shown to optimize hemodynamics during CPR and divert blood flow to the brain and heart with improved 24h survival, neurologic function, left ventricular function, and vital organ blood flow after prolonged cardiac arrest in pigs (10-12). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of SNP with mechanical CPR (SNPeCPR) has been proven to optimize hemodynamics during CPR and improve myocardial and neurologic function and therefore the survival outcome in animal studies (12,13). Based on the publication, in this issue of Critical Care Medicine, Debaty et al (14) investigated the effect of SNPeCPR on heat exchange during surface cooling in a prolonged ventricular fibrillation (VF) porcine model.…”
Section: Wwwccmjournalorgmentioning
confidence: 99%